Elevating Bangladesh: Exploring Tourism Marketing Strategies for Growth - Rahman, Shati Sarmin; Siddique, Shohana (Asian Business Review, 2023)
Bangladesh, with its pristine natural landscapes, rich historical heritage, and abundant archaeological treasures, presents an enticing prospect for tourism development. The tourism industry holds immense potential for driving economic growth, bolstering the nation's Gross Domestic Product (GDP), and generating foreign currency earnings. As countries worldwide vie for a share of the tourism market, effective marketing strategies become imperative for attracting visitors and maximizing revenues. This study investigates the current landscape of tourism marketing in Bangladesh, aiming to identify opportunities, challenges, and strategic interventions for sustainable growth. Through a comprehensive analysis of existing literature and empirical data, this research sheds light on the pivotal role of promotional activities in enhancing the competitiveness of Bangladesh's tourism sector. Key findings highlight the need for targeted investments, innovative marketing approaches, and policy support to capitalize on the country's tourism potential.